A hierarquia bacharelado/licenciatura em diferentes áreas do conhecimento: uma análise da UFMG - Lais Barbosa Patrocino (2013)
This study aimed to analyze the hierarchies between teaching and bachelor degrees in different areas of expertise of Universidade Federal de Minas Gerais (UFMG). We examined socioeconomic and cultural differences between students in both degrees that enter UFMG in 2010 in all undergraduate programs that comprised a teaching degree. Additionally students professional career disposition was analyzed. We examined students socioeconomic and cultural data from the Questionário Socioeconômico e Cultural da Comissão Permanente do Vestibular (COPEVE) filled in, by the prospective students, in the university admission exam. Thirty six interview were performed with purpose to analyze career aspirations with students in teaching and bachelor degrees of six courses of different areas of expertise of UFMG: Biological Sciences, Social Sciences, Physical Education, Physics, Geography and Letters. The results demonstrated that the socioeconomic and culture differences are higher between day and night shifts than between the modalities. We suggested that the hierarchy between teaching and bachelor degrees is perceived by the students in the symbolic perspective, and the way that they feel belonging to groups of high or low status is related to their cultural heritage and also their academic experience. In Biological Sciences and Physics, courses that demanded a higher level of academic performance in the university entrance exam, the idea of superiority of bachelor compared to teaching degree was more evident. In Letters course, which has a higher demand for teaching degree, the idea of superiority was less present. Geography and Social Sciences courses showed contradictory realities concerning the institutional incentive to teaching degree, the first characterized by the presence of specific forms of support and the second by the absence of them. Finally, the Physical Education course, which recently separated the two modalities in courses with their own structures, showed the greatest clarity about the aims and purposes of each one.